Strategic Maritime Boundaries for Trilateral Cooperation: Indonesia, Australia, and Papua New Guinea (Jurnal Lemhannas RI, 2024)
Purpose: This study examines the development of trilateral economic cooperation between Indonesia, Australia, and Papua New Guinea, focusing on maritime transport connectivity, fisheries management, and tourism and education collaboration. The research highlights how these initiatives can support regional integration and promote sustainable economic growth in border areas.Study Design/Methodology/Approach: The study employs a qualitative descriptive approach by analysing secondary data on transportation networks, fisheries production, and cross-border trade. It integrates theoretical perspectives on international trade, blue economy, and regional cooperation to evaluate the potential and challenges of trilateral partnerships.Findings: The study finds that improved sea route connectivity can reduce transportation costs, enhance export competitiveness, and stimulate investment and trade. Collaboration in fisheries can boost local livelihoods through increased production, job creation, and technology transfer. Furthermore, tourism and education cooperation can strengthen regional ties, improve human resource quality, and support sustainable economic development.Originality/Value: This study contributes to the literature on regional economic cooperation by providing insights into the strategic potential of trilateral partnerships in eastern Indonesia. It highlights practical recommendations for enhancing connectivity, fostering resource sustainability, and promoting social and economic development in maritime border areas.
Keywords: Connectivity; exports; fishery; marine resources; prosperity